PENGARUH EMPLOYEE ENGAGEMENT DAN KOMITMEN KARYAWAN TERHADAP KINERJA KARYAWAN BANK GENERASI Y - Puspa, Deisya Monika; Sagala, Ella Jauvani (Jurnal Manajemen, 2018)
The purpose of this study was to determine the effect of employee engagement and commitment to the performance of generation y employees at BRI Bank in Wonosobo Regency. The population in this study were employees of Bank BRI Wonosobo which were categorized as Generation Y (ages 18-38 years). The method applied in this study is a quantitative method. Based on the results of the test and data analysis, employee engagement and employee commitment have a significant effect on employee performance. The results of this study are expected to provide input for BRI Bank in Wonosobo Regency.